Biometric Based Web Security Using Ridges of Finger (International Journal of Engineering and Computer Science, 2013)
Web security is in general taken as providing safeguard at the borders of an organization by keeping out impostors. For this purpose password based verification system with public key cryptography is a common standard. Passwords however have their own weaknesses; not only weak passwords can be easily guessed but the strong ones can be broken through too. Sometime people use access cards or identity cards for authentication purpose which can easily be stolen or forged. So designing a high security using passwords, identity cards or access cards still remain an open problem. Biometric characteristics of an individual however are unique and do not change over time that makes biometrics well suited for authentication. There are a large number of applications of biometric system for authentication based on finger prints, hand geometry, iris and voice exist, such as forensics, driver license and passport control etc. Since the internet growth is increasing rapidly, restricted access to sensitive data on the Web to unauthorized users is needed. A hand geometry based system has been proposed here to authenticate users for imposing access restriction to web. This method has been tested on 100 individuals. This technique can be used for e-commerce, e-banking applications etc.